PETA INTERVENSI TERHADAP REMAJA SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN PENGAMBILAN KEPUTUSAN KARIR : LITERATUR REVIEW - Rofiq Husnul Maafi; Hosnul Abrori (Sociocouns: Journal of Islamic Guidance and Counseling, 2022)
Adolescence is a period of transition from childhood to adulthood. At this time a person will experience development both physically and psychologically. The task of adolescent development, among others, is to determine their future goals, one of the things that a teenager needs is the ability to make good career decisions. This study tries to find an intervention as an effort to improve the career decision-making ability of adolescents. This study uses the journal review method, which examines 10 journals that discuss issues that affect youth career decision-making abilities. So that in this study it was found that there are several treatments that can improve decision-making abilities, including: counseling using realty therapy techniques, group counseling cognitive information processing, career guidance, career-focused counseling, group guidance, trait and factor counseling, group guidance based on life skillsAdolescence is a period of transition from childhood to adulthood. At this time a person will experience development both physically and psychologically. The task of adolescent development, among others, is to determine their future goals, one of the things that a teenager needs is the ability to make good career decisions. This study tries to find an intervention as an effort to improve the career decision-making ability of adolescents. This study uses the journal review method, which examines 10 journals that discuss issues that affect youth career decision-making abilities. So that in this study it was found that there are several treatments that can improve decision-making abilities, including: counseling using realty therapy techniques, group counseling cognitive information processing, career guidance, career-focused counseling, group guidance, trait and factor counseling, group guidance based on life skills